2006
DOI: 10.1002/nau.20193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bladder dysfunction in Parkinsons disease

Abstract: The prevalence of severe LUTS was similar with other studies, but the correlation between Dan-PSS and stage of disease, and not IPSS indicates that despite seeing no increase in frequency and severity of LUTS as PD progresses, patients find symptoms more bothersome. This may be due to progression in gait difficulties or a decreasing ability to separate and integrate sensory input, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 39 publications
8
83
0
4
Order By: Relevance
“…Despite the potential imprecision associated with the use of a questionnaire that has not been validated, we do not think it has introduced significant errors in our study and other authors have used questionnaires developed for men to evaluate female patients in similar studies. 13,14 Among the factors possibly related to voiding disorders, we evaluated age, duration of PD and degree of neurological impairment caused by the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential imprecision associated with the use of a questionnaire that has not been validated, we do not think it has introduced significant errors in our study and other authors have used questionnaires developed for men to evaluate female patients in similar studies. 13,14 Among the factors possibly related to voiding disorders, we evaluated age, duration of PD and degree of neurological impairment caused by the disease.…”
Section: Discussionmentioning
confidence: 99%
“…14,33 The reason why many studies did not detect stroke as a correlate for nocturia might be a result of the low prevalence of stroke survivors among community-dwelling people (2-3%). 17,87 In several patient-based studies, it has been reported that nocturia is one of the most prevalent LUTS 115 and non-motor symptoms 116,117 of Parkinson's disease. Young et al reported that patients with severe Parkinson's disease had a significant increase in the number of nocturnal voidings compared with those with mild disease.…”
Section: Diseases Related To the Cnsmentioning
confidence: 99%
“…[101][102][103] These rates tend to be lower if MSA has been carefully eliminated from the study population, as LUTS are found in nearly all MSA patients. 104 The most widely accepted theory explaining LUTS pathogenesis in PD is that the loss of basal ganglia neurons disrupts normal inhibition of the micturation reflex (located in the pontine micturation center), mediated by D1 receptors.10 5 This loss of reflex inhibition leads to an unstable bladder, resulting in the urgency and frequency symptoms most often described by PD patients.…”
Section: Genito-urinary Systemmentioning
confidence: 98%
“…101 shown to affect bladder function, although there are conflicting reports as to whether they improve or worsen symptoms. 102,110 In general, these medications should not be considered as a primary treatment for de novo LUTS in PD patients.…”
Section: Genito-urinary Systemmentioning
confidence: 99%